A study of macro economy in determining the commercial property market - Sim, Boon Hun (2005)
The influence of macroeconomic variables toward real estate performance, as well as it effects on commercial property transaction is inevitable. As a result, the relationship propagates for this study in the endevor to understand and explain the influence of these macroeconomic variables. This study is set out to ascertain the commercial property performance, especially in its transaction volume. Hopefully, it will serve as a complement to other related studies carried out. The main purpose of this study is to develop a hypothesis for projecting trends of property transactions. It will be based upon an analysis of the relationship between key macroeconomic variables and property transaction. Several analytical methods such as correlation and regression analysis were carried out. Evaluation based on proportion of each macroeconomic variable was determined, and ultimately combined as a complete model to predict in a more acceptable manner. In this finding, it obviously showed that the existence of several trends were aimed to affect the commercial property transaction volume. As presented in this research, some of the macroeconomic variables varies in the way they influence the market. They significant ones include Gross Domestic Product, Base Lending Rate (During the economic crisis in year 1997), national saving and bank loan allocated to the property sector. In a significant way, this finding suggests that by monitoring the macroeconomic variables, the commercial property market performance is predictable, especially in its demands on the market. More Important, it will also contribute towards a sustainable development of new projects in the coming future.